Uji Aktivitas Ekstrak Buah Pare (Momordica Charantia) Sebagai Antibakteri dan Antifungi - Rahel Primasita Panala; Stevani Noviyanti Seran; Adriana Anteng Anggorowati; Shella Permatasari Santoso (Widya Teknik, 2022)
Green-antibacterial is another alternatif as an antibiotic. One of the natural ingredients which has green-antibacterial properties is bitter melon (Momordica charantia). Bitter melon has compounds that function as antibacterial, antifungal, antiviral and anti carcinogenic. This is due to bitter melon fruit has active compounds such as alkaloids, flavonoids, saponins, tannins, and phenols. In this research, bitter melon is maserated by aquadest in a various ratio weight per volume (w/v) 1:40, 1:20, 1:13,3 and 1:10 for 24 hours. Filtrate is filtered then dried for 10 hours to get the crude extract of biter melon. phytochemical test, measurement of total phenolic content (TPC), antibacterial and antifungal test. According to the result, bitter melon extract contain alkaloids, saponins and tanins with the highest value of total phenolic content measurement is the rasio of 1:10 scilicet 0,3390 g GAE/g sample. The strongest inhibition is found in ratio 1:10 with an average diameter is 14,5 ± 2,12 mm. Whilst, for the antifungal test, the inhibition zone is only found in the 1:13,3 and 1:10 ratios with an average diameters are 7±0,42 mm dan 8,65±0,071 mm.